2014
DOI: 10.1007/s10995-014-1509-9
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence, Power, and Equity Among Adolescent Parents: Relation to Child Outcomes and Parenting

Abstract: Intimate partner violence (IPV) victimization and perpetration and power imbalances in parenting partners may result in poor outcomes for parents and children. Previous work in this area has focused on the maternal experiences, neglecting to examine paternal effects. The present study aimed to elucidate the role of IPV, power, and equity in parenting and child outcomes in an urban sample of adolescent parents. 159 male and 182 female parents in a relationship were recruited through university-affiliated hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 49 publications
(59 reference statements)
0
25
0
Order By: Relevance
“…The abuse not only will traumatise the parent, but also will negatively impact the quality of parenting by the victim of the abuse (Gibson et al . ). Children born into families where abuse is present find themselves at risk for being the target of abuse or maltreatment; with Taylor et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The abuse not only will traumatise the parent, but also will negatively impact the quality of parenting by the victim of the abuse (Gibson et al . ). Children born into families where abuse is present find themselves at risk for being the target of abuse or maltreatment; with Taylor et al .…”
Section: Introductionmentioning
confidence: 97%
“…Social development of the child, along with the development of motor skills and moulding of the infant temperament, may be negatively impacted by the presence of IPV in adolescent mothers (Gibson et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…We identified six studies that assessed empowerment in cross-sectional/observational study designs and 19 studies that reported on empowerment interventions. Observational studies used mostly self-report or interview measures, such as the Decision-Making Dominance Subscale of the Sexual Relationship Power Scale [ 20 ] and critical ethnographic interviews [ 14 ]. Studies used different types of empowerment interventions (see Table 1 for details).…”
Section: Methodsmentioning
confidence: 99%
“…4245 Among adolescent parents, IPV was related to poor infant temperament and lower parenting competence, mediated by depression. 46 Children of parents experiencing violence are at risk for relational PTSD, which predicts that a child’s response to trauma is heightened because the parents’ responses are not well regulated. 47 Nearly half of the infants that have been exposed to parental IPV in their first year experienced at least one trauma symptom as reported by their mother.…”
Section: Introductionmentioning
confidence: 99%